Determining the deficit coefficient as a function of irrigation depth and distribution uniformity Determinação do coeficiente de déficit em função da lâmina de irrigação e da uniformidade de distribuição - Everardo C. Mantovani; Gregório G. Faccioli; Brauliro G. Leal; Luis C. Costa; Antônio A. Soares; Paulo S. L. Freitas (Revista Brasileira de Engenharia Agrícola e Ambiental)
The present study aimed at the development of the water deficit coefficient as a function of the Christiansen uniformity coefficient and relationship between the applied water depth and that required by a given crop, taking into account that the water distribution by the sprinkler follows a normal distribution. Another objective was to compare the experimental results to those obtained through simulation with the Mantovani model. For this, the water deficit coefficients developed in this work were used, as well as the simplified coefficient that takes into account the water distribution by the sprinkler following a uniform distribution, and finally the development of the production functions for the bean crop by using the Mantovani model. The production values simulated by the model, using the normal deficit coefficient, were always less than those simulated with the uniform deficit coefficient for all uniformity levels and all values of the crop's maximum evapotranspiration fraction restored by other sources (p). Under the conditions that this study was carried out, the use of the water deficit coefficient based on the normal distribution model did not provide a better performance of the simulation model proposed by Mantovani. Os objetivos primordiais neste trabalho foram: o desenvolvimento do coeficiente de déficit em função do coeficiente de uniformidade de Christiansen e da relação entre a lâmina aplicada e a lâmina requerida pela cultura, considerando-se que a distribuição de água pelo aspersor segue a distribuição normal, e a comparação dos resultados experimentais com os resultados obtidos por meio da simulação com o uso do modelo proposto por Mantovani, utilizando-se coeficientes de déficit desenvolvido no presente estudo e o coeficiente simplificado, que considera a distribuição de água pelo aspersor, seguindo a distribuição uniforme e, por último, o desenvolvimento das funções de produção para a cultura do feijão com o modelo desenvolvido por Mantovani. Os valores do rendimento simulados pelo modelo através do coeficiente de déficit normal, foram sempre inferiores aos valores simulados com o coeficiente de déficit uniforme, para todos os níveis de uniformidade e para todos os valores da fração da evapotranspiração máxima da cultura reposta por outras fontes (p). Nas condições de realização deste trabalho, a utilização do coeficiente de déficit baseado no modelo de distribuição normal não possibilitou maior precisão na utilização do modelo de simulação proposto por Mantovani.